Agricultural research and extension: trends and challenges in Peru and around the world (2015–2025) - Olano Camán, Yadhira Milagros (2025)
Agricultural extension, understood as producer-oriented guidance, is vital for driving technology adoption and sector development. This systematic review (2015–2025) examines global and national trends in agricultural research and extension, witha particular focus on Peru's policy landscape. Internationally, the U.S.A., China, and Europe are identified as leaders in scientific innovation, while Brazil excels regionally through its integrated approach to research, innovation, and extension. Agricultural research is still centralized in Lima on a national level, but expanding capability in areas like Amazonas, Junín, and Puno emphasizes how urgently decentralization is needed. By comparing national research output with MIDAGRI’s Agrarian Development Plan 2021–2030 and relevant Sustainable Development Goals (SDGs), the study reveals strong thematic alignment in innovation, food security, and climate adaptation. Crucially, however, significant shortcomings are identified in governance and the effective inclusion of small-scale producers. Based on these findings, this study recommends strengthening decentralized R&D investment, fostering interregional research networks, and promoting strategic collaboration among universities, local governments, and rural communities. Ensuring the active participation of producers in the innovation cycle is essential for building a more inclusive, resilient, and effective agricultural extension system aligned with sustainable development goals.